Implementasi Akad Musyaraah Mutanaqisah dalam Kredit Pemilikan Rumah pada Perbankan Syariah - Agustin, Dhea; Hastriana, Anna Zakiyah (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2024)
The demand for home ownership continues to rise, prompting Islamic banking to create financing products through the Musyarakah Mutanaqishah contract as an alternative in Home Ownership Credit. This study aims to analyze the implementation of the Musyarakah Mutanaqishah contract within the context of Islamic banking. The research method used is qualitative descriptive. The findings indicate that while the Musyarakah Mutanaqishah contract is expected to enhance home accessibility for the public, its implementation in Islamic banks does not meet the regulations set forth in Fatwa DSN-MUI No. 73/DSN-MUI/XI/2008, particularly concerning the lack of capital contribution. As a result, the contract is deemed void despite being legally valid. This research contributes to providing insights into the challenges faced in implementing the Musyarakah Mutanaqishah contract within the Islamic banking system in Indonesia.